Pengembangan Video Pembelajaran Penggunaan Koreksi Warna untuk Bekas Jerawat Kemerahan pada Tata Rias Wajah Cikatri/Cikatricia - Salsabilla Safira Wijaya; Nurina Ayuningtyas; Lilis Jubaedah (Journal on Education, 2024)
Makeup is the art of using cosmetic materials to create a role face. Cikatricia makeup is a science that studies in terms of camouflage imperfect facial parts such as defects, scars, pigmentation, and other facial abnormalities or deficiencies using cosmetics and special techniques. This study aims to produce a video learning development product that can later be used as an additional learning resource in the Special Makeup Course in Cikatricia Makeup learning. This study discusses the use of green Color Corrector to cover Post Inflammatory Erythema or reddish acne scars in Cikatricia Makeup. The method used in this study is the Research & Development (R&D) development method of the ADDIE model with a Likert scale. The procedures carried out in making Learning Videos are identifying student needs, determining design plans, preparation, production stages, post-production stages, evaluation, data processing, final results and dissemination of learning products. The results obtained from material experts were 91,57% and media experts were 82,40%. Based on these results, it can be concluded that the Learning Video is very suitable to be used as a reference and learning resource for Makeup students at Jakarta State University and the general public.